Exploring the Inclusivity of Admission Systems in A Private University: A Qualitative Analysis of Student Perceptions - Damayanti, Erma; Susandi, Deny Gunawan; Rakhmawati, Ditta Mustika (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study aims to explore students' perceptions of the admission system at a private university in Indonesia and its impact on their academic experiences, particularly in terms of inclusivity, financial challenges, and access to resources. The research uses a qualitative approach, employing semi-structured interviews with seven students from diverse socioeconomic backgrounds. The data were analyzed through thematic analysis to identify recurring patterns and themes related to students' experiences with the admission system. The findings reveal that while the university's admission system is viewed as inclusive due to its affordability and flexible payment options, students still face significant financial challenges. Many participants reported that despite the availability of payment plans, additional expenses, such as living costs and academic resources, remain a burden. Furthermore, students from lower-income backgrounds expressed feelings of exclusion due to unequal access to academic support and extracurricular activities. The study concludes that while the admission system helps students gain access to higher education, it falls short in addressing the broader financial and social challenges faced by students. To enhance inclusivity, the university should expand its support mechanisms to address both financial and social disparities, ensuring equal opportunities for all students to succeed.